ELISA in the multiplex era: potentials and pitfalls - Tighe, Patrick J.; Ryder, Richard R.; Todd, Ian; Fairclough, Lucy C. (Wiley, 2015)
Multiplex immunoassays confer several advantages over widely adopted singleplex immunoassays including increased efficiency at a reduced expense, greater output per sample volume ratios and higher throughput predicating more resolute, detailed diagnostics and facilitating personalised medicine. Nonetheless, to date, relatively few protein multiplex immunoassays have been validated for in vitro diagnostics in clinical/point-of-care settings. This review article will outline the challenges, which must be ameliorated prior to the widespread integration of multiplex immunoassays in clinical settings: (i) biomarker validation; (ii) standardisation of immunoassay design and quality control (calibration and quantification); (iii) availability, stability, specificity and cross-reactivity of reagents; (iv) assay automation and the use of validated algorithms for transformation of raw data into diagnostic results. A compendium of multiplex immunoassays applicable to in vitro diagnostics and a summary of the diagnostic products currently available commercially are included, along with an analysis of the relative states of development for each format (namely planar slide based, suspension and planar/microtitre plate based) with respect to the aforementioned issues.